(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article examines the financial relations of economic entities in the financial management system. A definition of financial relations, their essence and types is given. The main directions of managing financial relations within the framework of financial management are analyzed. Financial analysis is considered as a tool for managing financial relations.